2023
DOI: 10.3389/fcosc.2023.1206832
|View full text |Cite
|
Sign up to set email alerts
|

Recovery and genotyping ancient Sicilian monumental olive trees

A. Marchese,
F. Bonanno,
F. P. Marra
et al.

Abstract: The long-lived and evergreen olive tree dominates the Mediterranean landscape, representing an agroecological and cultural symbol and a genetic heritage of inestimable value. Sicily, for historical, geographical, and cultural reasons, has a very rich and distinctive olive germplasm. In this work, a large survey was conducted to discover, collect, and characterize the genetic diversity of centennial monumental olive trees from historical sites, such as the Greek Temple Valley (Agrigento), ancient gardens, or fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 73 publications
(94 reference statements)
0
6
0
Order By: Relevance
“…Nevertheless, in certain areas of Galicia, olive groves continued to form part of the traditional agricultural landscape, although often as a marginal crop due to their location on steep slopes or poorly developed soils. This adaptation to different pedoclimatic contexts has favored the emergence of new genotypes or heterogeneous regional populations that are highly different at the morphological, molecular, and agronomic levels [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, in certain areas of Galicia, olive groves continued to form part of the traditional agricultural landscape, although often as a marginal crop due to their location on steep slopes or poorly developed soils. This adaptation to different pedoclimatic contexts has favored the emergence of new genotypes or heterogeneous regional populations that are highly different at the morphological, molecular, and agronomic levels [14].…”
Section: Introductionmentioning
confidence: 99%
“…Molecular markers, especially microsatellites (SSR), have been successfully used to identify monumental, ancient native or locally cultivated olive trees throughout the Mediterranean Basin in Algeria [21,22], Montenegro [23,24], Italy [14,25,26], Greece [27,28], Turkey [29,30], the Maltese Islands [31], and Spain [1]. These markers have also proven to be very suitable for germplasm collection management [2,[32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Other works that genetically characterized ancient olives trees in Mediterranean countries like Cyprus (Anestiadou et al, 2017), Israel (Barazani et al, 2014), Italy (Baldoni et al, 2006;Erre et al, 2010;Marchese et al, 2023), Malta (Valeri et al, 2022), Montenegro (Lazovićet al, 2016), or Morocco (El Bakkali et al, 2013, also reported that only a small proportion of them matched to known olive cultivars. In agreement with the conclusion of these authors, our findings support that the ancient olives trees deserve a careful consideration and conservation measures as in-situ reservoir of olive genetic diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this loss of diversity weakens the availability of a potentially valuable strategic reserve for breeders that could help for dealing with future challenges such as temperature increase (potentially leading to a lack of chilling requirements for flowering and/or heat stress), water stress, salinity, emerging pests and diseases, farming in new edaphoclimatic areas, and new market trends such as the search for specific quality characters in EVOO (Peŕez et al, 2019;Medina-Alonso et al, 2020;Serrano et al, 2020;Lorite et al, 2022). For these reasons, the recovery, conservation and study of minor cultivars is of increasing interest in Spain and elsewhere (Dıéz et al, 2011;Hmmam et al, 2018;Ninot et al, 2018;Debbabi et al, 2020;Valeri et al, 2022;Marchese et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Although among the molecular markers, microsatellite or SSR (Simple Sequence Repeats) represent the marker of choice for fingerprinting study and a powerful instrument for germplasm management, allowing diversity assessment among standardized databases (e.g. peach - Marchese et al 2005;palm -Giovino et al 2021palm -Giovino et al , 2023fig -Costa et al 2017;apple -Venison et al 2022;sweet cherry -Ordidge et al 2021;Trifonova et al 2021;almond -Dangl et al 2009;Cimò et al 2017;hazelnut -Fiore et al 2022;olive -Atrouz et al 2021;Marchese et al 2023), in the carob species La Malfa et al (2014) found low genetic diversity by using a set of EST-SSR. Viruel et al (2018) tried to improve the detection of diversity by using next-generation sequencing of SSR loci, screening populations throughout the Mediterranean Basin -from Spain, Greece, Lebanon, and Morocco.…”
Section: Introductionmentioning
confidence: 99%